Salivary microbiota of HIV-positive children and its correlation with HIV status, oral diseases, and total secretory IgA - CARINA SILVA-BOGHOSSIAN, GLÓRIA FERNANDA CASTRO, RICARDO PALMIER TELES, IVETE P. R. DE SOU (IAPD and Blackwell, 2008)
Human immunodeficiency virus infection leads to a progressive decrease in the number and function of the CD4+ T lymphocytes, depressing the immune response and leaving the host susceptible to many opportunistic infections.